Validation and potential refinement of the Malaysia Medication Adherence Assessment Tool (MyMAAT) among patients with non-dialysis chronic kidney disease - Ming Chiang Lim; Ernieda Hatah; Jia Ean Goh; Ahmad Ramdani Abd Manan; Joyce Chu Yee Tan (PLoS ONE, 2025)
Background Medication adherence is essential for managing chronic kidney disease (CKD) and preventing its progression. In Malaysia, adherence is commonly assessed using the 12-item Likert scale Malaysia Medication Adherence Assessment Tool (MyMAAT-12), but it has not been validated for CKD patients. Thus, this study aimed to validate and explore its potential for item reduction among non-dialysis CKD patients. Methods and findings A cross-sectional, multi-center study was conducted across eight health facilities in Pahang state from December 2023 to August 2024. Non-dialysis CKD patients aged 18 years and above, with or without diabetes, attending outpatient clinics, were given the 12-item self-administered MyMAAT-12 and items from the Beliefs about Medicines Questionnaire (BMQ). Patient demographics, HbA1c levels, and serum phosphate changes within three months preceding MyMAAT-12 completion were collected. The dimensionality of the scale was explored through exploratory factor analysis (EFA), and its reliability and criterion validity were evaluated to ensure robust measurement properties. A simulation test was conducted to explore the feasibility of reducing MyMAAT-12 to a shorter version. A total of 246 respondents participated, predominantly female (54.5%) and Malay (91.5%), with a mean age of 59.5 ± 12.5 years and an average CKD duration of 5.0 ± 5.4 years. The average medication adherence score was poor to moderate (<54/60). MyMAAT-12 demonstrated excellent internal consistency (Cronbach’s alpha = 0.90) and significant association with BMQ categories (χ²(2) = 16.8, p < 0.01). EFA identified a two-factor structure. MyMAAT-12 adherence categorization was significantly associated with HbA1c% (<8% vs. ≥ 8%) (χ2(2) = 4.7, p = 0.03) and phosphate level changes (χ2(2) = 5.48, p = 0.02). Results indicated that reducing MyMAAT-12 to a 7-item scale was feasible, while maintaining strong psychometric properties (Cronbach’s alpha = 0.87) and a significant association with HbA1c% (ρ = −0.22, p = 0.01). Conclusion MyMAAT-12 demonstrated strong reliability and validity, making it a valuable tool for clinicians to accurately assess medication adherence in non-dialysis CKD patients. The shortened MyMAAT-7 offers a streamlined alternative with strong psychometric properties, enhancing clinical practicality.